Characterization of complex organelles and the dissection of a pyrenoidal red-type rubisco activation system of diatoms - Schober, Alexander Fabian (Nanyang Technological University, 2020)
Diatoms are a large group of unicellular microalgae that derived from secondary endocytobiosis, and consequently operate photosynthesis and carbon fixation in the context of a peculiar metabolism. Their mitochondria accommodate unique remnants of their evolutionary past, such as a partial mitochondrial glycolysis or a bacterial Entner-Doudoroff pathway. Their plastids are surrounded by four membranes, and possess pyrenoids that are involved in an elaborate biophysical carbon concentrating mechanism. So far, it is not understood how the first step of the Calvin cycle, the reaction catalyzed by the rubisco, is regulated. However, the concentrations of ATP and NADPH in plastids and mitochondria, which are needed to fix carbon dioxide, where shown to be highly balanced via a tight interconnection between plastidal and mitochondrial metabolism. This work addresses several fundamental aspects of the diatom metabolism in order to gain a better understanding of diatoms photosynthesis and its regulation, with a major focus on carbon acquisition. Firstly, we established two methods for the independent purification of plastid and mitochondria fractions from the diatom Thalassiosira pseudonana. By a combination of physiological and molecular techniques, we demonstrate that the obtained organelles remain structurally intact, performing oxygenic photosynthesis and mitochondrial respiration, respectively. A bioinformatic pipeline was established in order to identify organellar proteins experimentally for mapping metabolic pathways, assessing light harvesting pigments, reassigning ‘GreenCut proteins’ and for testing existing targeting prediction programs. Secondly, we address aspects of regulation and maintenance of photosynthesis in diatoms. The CO2-fixing enzyme rubisco is highly susceptible to dead-end inhibition by its own substrate RuBP and a variety of photosynthetic misfiring products. In plants, red algae and some photosynthetic bacteria, this inhibition is release by a diverse class of AAA+ remodeling chaperones, termed rubisco activases. It was yet unknown whether a similar regulation exists in diatoms. Here we provide a comprehensive characterization of a so far undescribed pyrenoidal heterooligomeric red-type rubisco activation system in diatoms. By heterologous protein expression and native purification of activase protein, we demonstrate that a 1:1 oligomer formation of activase complexes between a plastid and a nucleus encoded isoform occurs, and that complexes are required to restore inhibited diatom rubisco. Domain-deletion experiments on fluorescently labeled rubisco activase protein allowed the investigation of a novel N-terminal low complexity region that is essential for intracellular localization in diatoms. Comprehensive biochemical analyses further imply tightly regulated ATPase kinetics and activase oligomerization, and suggest that the mechanism of rubisco restoration most likely is conserved in organisms of the red-plastid lineage.